Il bambino di ieri: breve storia di una storiografia - Becchi, Egle (Studi sulla Formazione/Open Journal of Education, 2011)
Feelings between idea and emotion: The author reflects on these themes linking their reflection in the world of childhood. The French trials are very important with regard to the social history of childhood and the researcher begins by the work of Aries continuing in areas of more recent and pedagogically significant There are important references, within the essay, to the child of the past in the historiography of across the Atlantic There are important references within the essay, to the child of the past in historiography ‘s across the Atlantic and the essay becomes an important source of significant debate and Technical Symposium.